Evaluation of Konselopoly Quest as Educational Media in Riverside Schools Through the CIPP Model - Muhammad Syauqie Rizaldin; Hendro Yulius Suryo Putro; Muhammad Arsyad (Sebatik, 2026)
This study purpose to evaluate the implementation of Konselopoly Quest as an educational medium in riverside schools using the Context, Input, Process, and Product (CIPP) evaluation model. A qualitative approach was employed involving students from SMA Negeri 12 Banjarmasin selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation and analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that, in the context dimension, the game successfully created a more engaging and interactive learning environment, although the content was not fully aligned with students’ academic needs. In the input dimension, the visual design and overall appearance were perceived positively, while the use of foreign terms and game mechanics required further simplification. In the process dimension, the game enhanced students’ social interaction, teamwork, participation, and critical thinking skills, despite uneven levels of involvement influenced by group dynamics. In the product dimension, the game contributed positively to students’ understanding of Pancasila Student Profile values, social skills, and self-confidence. However, its impact on long-term learning motivation and comprehensive understanding of wetland environments remained limited. Overall, Konselopoly Quest was found to be a reasonably effective educational medium that promotes active, communicative, and enjoyable learning experiences, although improvements are still needed in terms of content, language, game mechanics, and implementation strategies.